Seismic investigations of firn in Antarctica - Hannes Hollmann (2023)
The firn layer represents the natural interface between glacier ice and the atmosphere. Firn is a highly heterogeneous medium, where the interplay of physical processes on the microscale determines its evolution on the macro-scale. Determining firn characteristics provides insight into weather and climate history, active glacier processes, and knowledge of firn depth and density is crucial for the accurate assessment of ice mass changes of major ice sheets. Direct constraints on firn structure, however, are limited to a few locations in Antarctica as the acquisition of firn cores or borehole-based measurements has a high logistic cost. Seismic surveys are one example of a geophysical method that can be used to determine some firn properties, at a lower resolution, with efficiency in field logistics. Such surveys have the potential to improve the spatial coverage of firn measurements, particularly for Antarctica. The research documented in this thesis firstly investigates the firn layer of the Amery Ice Shelf, at the confluence of two ice streams, using a seismic refraction approach together with the Wiechert-Herglotz method. Field data from seismic surveys carried out in the along-flow and across-flow directions are examined revealing differences in travel times according to survey line orientation and the upstream origin of the ice stream flow. The firn acts as a means of recording glacier processes and shows evidence for seismic anisotropy. The findings are consistent with dynamic coupling between the firn and the underlying ice. Subsequent studies documented in the thesis further investigate the use of seismic refraction methods applied to firn, and the firn-ice transition zone. Computation-based numerical experiments are carried out to understand the sensitivity of the inferred results to workflow and modelling parameter choices, and to inform the use of the WH method to characterise the depth and seismic structure of firn. A large-scale study of firn layer density determination is then presented, informed ...